Dataset for the estimation of a new body fat measurement method (2021)
Due to the increasing prevalence of obesity and its nega- tive consequences worldwide on public health, body compo- sition analysis is a central pillar to assess the nutritional sta- tus. Scientists could use datasets to develop a new body fat measurement formula. Using bioelectrical impedance analy- sis, we analyzed the total body composition of 345 patients (234 men and 111 women) aged between 18 and 60 years residing in the metropolitan area of Barranquilla, Colombia. They have the potential for predictive formula analysis en- hancing the cooperation among scientists. Due to the obesity pandemic, new datasets from other populations are needed to develop a body fat basic mathematical equation formula that could be used worldwide to determine the prevalence of overweight and obesity in a specific population group pre- disposed to develop metabolic syndrome or death, secondary to high cardiovascular risk.